Condenser-Based Instant Reflectometry - Lan, Yanxiang; Dong, Yue; Wang, Jiaping; Tong, Xin; Guo, Baining (Computer Graphics Forum, 2010)
We present a technique for rapid capture of high quality bidirectional reflection distribution functions(BRDFs) of surface points. Our method represents the BRDF at each point by a generalized microfacet model with tabulated normal distribution function (NDF) and assumes that the BRDF is symmetrical. A compact and light-weight reflectometry apparatus is developed for capturing reflectance data from each surface point within one second. The device consists of a pair of condenser lenses, a video camera, and six LED light sources. During capture, the reflected rays from a surface point lit by a LED lighting are refracted by a condenser lenses and efficiently collected by the camera CCD. Taking advantage of BRDF symmetry, our reflectometry apparatus provides an efficient optical design to improve the measurement quality. We also propose a model fitting algorithm for reconstructing the generalized microfacet model from the sparse BRDF slices captured from a material surface point. Our new algorithm addresses the measurement errors and generates more accurate results than previous work. Our technique provides a practical and efficient solution for BRDF acquisition, especially for materials with anisotropic reflectance. We test the accuracy of our approach by comparing our results with ground truth. We demonstrate the efficiency of our reflectometry by measuring materials with different degrees of specularity, values of Fresnel factor, and angular variation.